Common information-processing irrationality as trade creator - Bogdan Klishchuk (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2020)
We show that a common (identical across investors) irrationality in information processing can be enough to create nontrivial trade, using one of standard partial-equilibrium environments. We can attribute this trade to their common irrationality because we strip the investors and their circumstances of all heterogeneities but purely age (in a sense experience), make investment horizon age-independent, and keep all information complete. The common irrationality in our model takes the form of a somewhat non-Bayesian information processing. The resulting trade between such essentially identical individuals with the very same irrationality in their information processing can also feature different kinds of mispricing.
Keywords: 330; Aktienmarkt; Wertpapierhandel; Anlageverhalten; Entscheidung unter Unsicherheit; Information; Rationalität; Theorie